2017
DOI: 10.1111/eff.12390
|View full text |Cite
|
Sign up to set email alerts
|

Migration and movement profiles of a potadromous fish (Brachymystax lenok Pallas 1773) in a highly connected river system (Mongolia)

Abstract: Understanding a species' spatial and temporal movements along with the way these shift under extreme environmental conditions is vital for developing scientifically sound conservation and management strategies. The aim of this research was to describe and quantify the seasonal migration patterns and fine-scale movement profiles of Brachymystax lenok, a threatened, potadromous salmonid that inhabits the highly connected, boreal river basins of Siberia and northern Asia. During this study 21 mature individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
2
4
0
1
Order By: Relevance
“…However, despite this shared haplotype, most of the genetic differentiation for B. lenok was distributed among basins (Froufe et al, 2008;Liu, Kunag, Tong, & Yin, 2011;Xia et al, 2006), which indicated large-scale, intrabasin gene flow within these vast, unfragmented river systems. However, B. lenok was the only species to demonstrate isolation by distance within both river basins, which is in line with the expectation of a reduced dispersal ability compared to the larger sized H. taimen (Yoon et al, 2014;Gilroy et al, 2010;Kaus et al, 2017).…”
Section: Genetic Population Structure and Conservation Priorities Fsupporting
confidence: 84%
See 2 more Smart Citations
“…However, despite this shared haplotype, most of the genetic differentiation for B. lenok was distributed among basins (Froufe et al, 2008;Liu, Kunag, Tong, & Yin, 2011;Xia et al, 2006), which indicated large-scale, intrabasin gene flow within these vast, unfragmented river systems. However, B. lenok was the only species to demonstrate isolation by distance within both river basins, which is in line with the expectation of a reduced dispersal ability compared to the larger sized H. taimen (Yoon et al, 2014;Gilroy et al, 2010;Kaus et al, 2017).…”
Section: Genetic Population Structure and Conservation Priorities Fsupporting
confidence: 84%
“…This unique B. lenok phylogroup is genetically distinct and thus highly valuable in the context of genetic conservation for the species. Incidentally, this group has also been the focus of increased scientific research on B. lenok including studies on their feeding ecology (Olson, Jensen, & Hrabik, ), thermal tolerances (Hartman & Jensen, ), lotic and lentic growth comparisons (Tsogtsaikhan et al, ), and seasonal movements (Kaus, Büttner, Karthe, Schäffer, & Borchardt, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these rivers generally lack impoundments and introduced species. The available literature on fish assemblages in Mongolian rivers is scarce, with fish assemblages only being explored in a few publications, including identification and occurrences (Kottelat, 2006;Mendsaikhan et al, 2017), ecology (Kaus et al, 2018;Mendsaikhan et al, 2016;Mercado-Silva et al, 2008;Olson et al, 2016), conservation (Jensen et al, 2009), and genetics (Dulmaa et al, 2016;Kaus et al, 2019;Roman et al, 2018). However, variation of fish assemblages at the scale of entire river networks is largely unknown for most Mongolian drainages.…”
Section: Introductionmentioning
confidence: 99%
“…Данная особенность может быть адаптивной поведенческой реакцией рыб на сложные сезонные условия водной среды [11]. Показано [11,22,31,32], что глубина, скорость придонных течений являются важными предикторами выбора среды обитания в зимний период для рыб, в том числе и представителей семейства Acipenseridae, поскольку глубоководная среда обитания обеспечивает убежище для этих рыб, а низкоскоростные участки обеспечивают сохранение энергии в состоянии покоя.…”
Section: обсуждение результатовunclassified